Utilization of Artificial Intelligence in Mathematics Education: Perspectives from Professors and Doctoral Students in Indonesia - Fadhil Zil Ikram; R. H. Yanti Silitonga; Rosidah; Mei Radia Putri (Indonesian Technology and Education Journal, 2026)
Artificial intelligence (AI) is increasingly integrated into higher education, yet comparative studies of how doctoral students and professors view AI in mathematics education remain scarce, particularly in Indonesia. This study explores the perspectives of both groups through a qualitative design involving focus group discussions and semi-structured interviews with eight doctoral students and two mathematics education professors at several public universities. Data were analysed through condensation, presentation, and verification, with triangulation and member-checking ensuring credibility. Five interpretative patterns emerged: (1) heterogeneous AI adoption among doctoral students, ranging from extensive to restrictive-reflective; (2) shared epistemological grounding that AI functions as a tool rather than a substitute for conceptual mastery; (3) a proposal for differential course regulation, distinguishing a 'no AI' category for conceptual courses from a 'maximum AI' category for technology-based courses; (4) asymmetric control strategies that can be bridged through a disclosure-and-verification paradigm; and (5) complementary ethical concerns across roles. Participants also showed limited awareness of AI's potential as conversational, pedagogical, and teachable agents. While the small sample limits generalisability, these findings offer preliminary insights into how AI use is negotiated within supervisor–student relationships and suggest directions for further inquiry into AI adoption in Indonesian doctoral programmes in mathematics education.